2015
DOI: 10.1017/s0950268815002708
|View full text |Cite
|
Sign up to set email alerts
|

Disease burden of congenital cytomegalovirus infection at school entry age: study design, participation rate and birth prevalence

Abstract: Congenital cytomegalovirus infection (cCMV) may lead to symptoms at birth and long-term consequences. We present a nationwide, retrospective cohort study on the outcome of cCMV up to age 6 years. For this study we identified cCMV, using polymerase chain reaction, by analysing dried blood spots, which are taken shortly after birth for neonatal screening. The group of children with cCMV were compared to a group of children who were cCMV negative at birth. Data were collected about their health and development up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 37 publications
0
38
0
Order By: Relevance
“…A study that looked at RSV hospitalizations among commercially and Medicaid insured infants also found higher rates of hospitalizations and more severe cases among Medicaid-insured infants 16 . Data from this study and others suggest that not all infants with symptomatic congenital CMV disease are diagnosed or captured using administrative healthcare claims 17, 18 . We observed a prevalence of symptomatic congenital CMV disease that was between one-half and one-third of the expected 5.0–7.5 per 10,000 prevalence in the United States 2 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A study that looked at RSV hospitalizations among commercially and Medicaid insured infants also found higher rates of hospitalizations and more severe cases among Medicaid-insured infants 16 . Data from this study and others suggest that not all infants with symptomatic congenital CMV disease are diagnosed or captured using administrative healthcare claims 17, 18 . We observed a prevalence of symptomatic congenital CMV disease that was between one-half and one-third of the expected 5.0–7.5 per 10,000 prevalence in the United States 2 .…”
Section: Discussionmentioning
confidence: 85%
“…We observed a prevalence of symptomatic congenital CMV disease that was between one-half and one-third of the expected 5.0–7.5 per 10,000 prevalence in the United States 2 . One study by Diener et al 19 found that the proportion of diagnosed symptomatic congenital CMV cases may be as high as 30%, though other studies have found this proportion to be much lower, with <10% of symptomatic cases diagnosed 17, 18, 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Details of the CROCUS study's design have been published previously . In short, children with and without cCMV were retrospectively identified.…”
Section: Methodsmentioning
confidence: 99%
“…When this was positive, a second, different, internally controlled quantitative polymerase chain reaction performed in triplicate was used for confirmation in cCMV‐positive children. This was also done in the selected cCMV‐negative comparison group . cCMV‐positive was defined as a positive result in both the screening and confirmation test.…”
Section: Methodsmentioning
confidence: 99%
“…The study design has been published elsewhere 11. Parents of 73 693 children, born between 1 January and 30 September 2008, living in the Netherlands were invited to participate in the study between October 2012 and January 2013.…”
Section: Methodsmentioning
confidence: 99%